Indigenous Knowledge on Ethnobotanical Plants of Kavrepalanchowk District - Malla, Birendra; Chhetri, R. B. (Kathmandu University Journal of Science, Engineering and Technology, 2009)
Ethnobotanical knowledge is common and important among the tribal people but much of the information is empirical at best lacking logical validation. A number of ethnic communities residing in the study area are partially or fully dependent on the forest resources to meet their requirements. The present study analyses indigenous knowledge of ethnobotanical plant species and utilization of 68 species belonging to 59 genera under 37 families in day-to-day life of ethnic communities of Kaverpalanchowk district of central Nepal. The diverse ethnic communities such as Tamang, Newar, Magar, Chhetri, Pariyar, Biswakarma, and Tolange have a good association with plants and their potential role they use for different purposes; treatment of various ailments, economic and other values, and worship in different religions and customs. The traditional knowledge on the utilization of these ethnobotanical plants is widely accepted by these indigenous people.